EVALUASI PELAKSANAAN PEMUNGUTAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN (PPH) PASAL 22 WAJIB PUNGUT BUMN PADA PT. TELEKOMUNIKASI INDONESIA CABANG MANADO - Salaki, Romullo Matthew; Sabijono, Harijanto (Universitas Sam Ratulangi, 2020)
Taxation is the sector that produces the most in an effort to increase state revenue. Through taxation, Indonesia is better able to submit requests for national development and other sector allocations. The appropriate method used in the special tax sector is a tax collection system that memebri for taxpayers, collect, deposit, and report the tax payable to the state treasury. The purpose of this study was to study the Evaluation of the Implementation of Collection, Depositing and Reporting of Income Tax Article 22 Obligatory SOE Levies at PT. Telekomunikasi Indonesia, Manado Branch. This research uses a descriptive qualitative research system. The results of research at PT. Telekomunikasi Indonesia, Manado Branch, can be accessed by collecting, depositing, and reporting income tax PP 22 mandatory SOE levies using a self-assessment system that is a tax collection system that authorizes taxpayers in the regulation of applicable tax invitations.